2023
DOI: 10.12659/ajcr.938651
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System and Cardiac Abnormalities in the Setting of a De Novo Heterozygous Col4a1 Variant

Abstract: Rare disease • congenital defects/diseases • rare coexistance of disease or pathology Background:The Col4a1 gene encodes a portion of type IV collagen, a major component of the tissue basement membrane.Col4a1 mutations are rare, most frequently affect neonates, and occur at a de novo mutation rate between 27% and 40%. Mutations are commonly missense and pleiotropic, presenting with cerebrovascular, renal, ophthalmological, and muscular abnormalities, collectively known as Gould Syndrome. Cerebral small vessel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…According to Whittaker et al, stroke is the most common cerebral manifestation in COL4A1-mutated patients, and in most cases, it is the hemorrhagic type [54]. Sometimes, hemorrhagic strokes and other fetal abnormalities might be found in prenatal ultrasound and then confirmed after birth [55]. Lafranconi et al in their systematic review reported white matter hyperintensities on MRI scans in patients aged from 7 days to 68 years, while the mean age of hemorrhagic stroke was around 32 years (range 14-49 years old) [56].…”
Section: Col4a1mentioning
confidence: 99%
“…According to Whittaker et al, stroke is the most common cerebral manifestation in COL4A1-mutated patients, and in most cases, it is the hemorrhagic type [54]. Sometimes, hemorrhagic strokes and other fetal abnormalities might be found in prenatal ultrasound and then confirmed after birth [55]. Lafranconi et al in their systematic review reported white matter hyperintensities on MRI scans in patients aged from 7 days to 68 years, while the mean age of hemorrhagic stroke was around 32 years (range 14-49 years old) [56].…”
Section: Col4a1mentioning
confidence: 99%